Lithium iron phosphate positive electrode material and preparation method thereof
Patent Information
- Application Number
- CN202610942594.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-16
AI Technical Summary
然而,该方法中水解生成的氟化锂在后续高温烧结过程中虽能促进颗粒球形化,但同样会过度活化晶界迁移,导致一次晶粒异常长大
[0025]This invention simultaneously introduces boron and titanium sources into the synthesis system of lithium iron phosphate (LFP). After mixing and sintering, a unique boron-titanium composite modification layer is designed and formed on the surface of LFP particles. Through the synergistic surface modification of boron and titanium, on the one hand, the low-temperature liquid phase formed by boron during sintering promotes the sphericity of LFP particles, significantly improving the compaction density and volumetric energy density of the powder; on the other hand, titanium is enriched on the particle surface to form a high-ionic-conductivity interface phase containing LiTi2(PO4)3, effectively suppressing excessive grain growth caused by the introduction of boron, while constructing a three-dimensional lithium-ion transport channel, greatly improving the interfacial kinetics and rate performance, and reducing side reactions between the electrode and the electrolyte. Ultimately, the material maintains high compaction density while possessing excellent cycle stability and high-rate discharge capability, making it suitable for the preparation of ultra-high energy density battery cells.
Smart Images

Figure CN122930902A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a lithium iron phosphate cathode material and its preparation method. Background Technology
[0002] Lithium iron phosphate (LiFePO4) cathode materials possess excellent stability, long cycle life, and low cost, leading to a continuously increasing market share. However, due to multiple factors such as the material's bulk structure and manufacturing process, its key properties, including compaction density and rate capability, have consistently lagged behind. Improving its volumetric energy density and rate capability during product iteration is crucial for current industry upgrading.
[0003] To improve the compaction density and kinetic performance of lithium iron phosphate (LFP) batteries, existing technologies often employ elemental doping or surface coating. Boron (B) modification is a known method, as it forms a liquid phase during sintering, reducing the surface activation energy of the particles and promoting sphericity. However, in-depth research indicates that while introducing boric acid (or borate) alone promotes particle rounding, it can also lead to excessive grain growth. Overly large particles prolong the solid-phase diffusion path of lithium ions, resulting in decreased capacity retention under high-rate or long-term cycling conditions, thus limiting its application in high-performance cells.
[0004] Chinese patent CN119430116A discloses a method for preparing spherical boron-doped lithium iron phosphate cathode materials. This method uses boride, a product of the slow hydrolysis of lithium borate fluoride, as a boron source and fluoride as a flux to achieve uniform boron doping and control the morphology of lithium iron phosphate particles. Ultimately, the resulting lithium iron phosphate cathode material exhibits a regular spherical particle shape and excellent electrochemical performance. However, while the lithium fluoride generated during hydrolysis promotes particle sphericity during subsequent high-temperature sintering, it also over-activates grain boundary migration, leading to abnormal primary grain growth. Although the particle roundness is improved, the coarsening of the internal grains prolongs the solid-phase diffusion path of lithium ions, limiting further improvements in rate performance.
[0005] Therefore, how to effectively improve the roundness and compaction density of lithium iron phosphate particles while precisely controlling grain growth and enhancing the stability of the particle surface structure has become a technical challenge that urgently needs to be solved in the preparation of lithium iron phosphate materials with both high energy density and long lifespan. Summary of the Invention
[0006] In view of the above problems, the present invention provides a lithium iron phosphate cathode material and its preparation method, which improves the roundness and compaction density of lithium iron phosphate particles while precisely controlling grain growth and enhancing the stability of particle surface structure.
[0007] The technical solution adopted by this invention to solve its technical problem is:
[0008] A first aspect of the present invention provides a lithium iron phosphate cathode material, comprising a lithium iron phosphate matrix and a boron-titanium composite modification layer coated on the surface of the lithium iron phosphate matrix.
[0009] Furthermore, the boron-titanium composite modification layer contains boron and titanium elements.
[0010] Furthermore, in the boron-titanium composite modification layer, the mass ratio of boron to titanium is 1:(1~4).
[0011] A second aspect of the present invention provides a method for preparing a lithium iron phosphate cathode material, comprising the following steps:
[0012] S1: Preparation of lithium iron phosphate matrix: Iron source, lithium source and carbon source are added to solvent in sequence and dispersed evenly to obtain slurry; the slurry is ball-milled and dispersed, and then nano-milled to the target particle size; after spray drying, it is sintered in roller kiln to obtain lithium iron phosphate matrix;
[0013] S2: Preparation of boron-titanium mixed solution: Add boron source and titanium source to deionized water and stir to form boron-titanium mixed solution;
[0014] S3: Mixing: The lithium iron phosphate matrix obtained in step S1 is added to a high-speed mixer and spray-mixed with the boron-titanium mixed solution obtained in step S2 to obtain a boron-titanium / lithium iron phosphate precursor.
[0015] S4: Sintering: The boron-titanium / lithium iron phosphate precursor obtained in step S3 is sintered in a nitrogen or argon atmosphere to obtain a lithium iron phosphate cathode material with a boron-titanium composite modification layer on the surface.
[0016] During sintering, boron forms a low-temperature liquid phase, effectively reducing the surface energy of lithium iron phosphate grains, promoting particle rearrangement and spheroidization, reducing sharp edges, and thus significantly improving the powder compaction density of the material. Simultaneously, titanium tends to accumulate on the particle surface or at grain boundaries during sintering, existing as nanoscale LiTi2(PO4)3 (with three-dimensional lithium-ion channels) or other titanium oxide compounds. Titanium enrichment serves two purposes: firstly, it pins grain boundaries, providing a reverse constraint force while boron promotes growth, preventing abnormal particle growth and maintaining particle size within an appropriate range; secondly, the formed titanium-containing interface phase possesses excellent lithium-ion conductivity, constructing a high-ionic-conductivity interface that promotes lithium-ion entry and exit from lithium iron phosphate particles, significantly increasing the interfacial lithium-ion migration rate. Furthermore, titanium enhances surface stability, enabling the composite modification layer to effectively reduce side reactions between the electrode material and the electrolyte, thereby improving cycle stability.
[0017] Through synergistic modification with boron and titanium, boron effectively solves the problem of insufficient compaction density, while titanium compensates for the potential degradation in cycle and rate performance caused by the introduction of boron. This synergistic effect allows the material to maintain excellent kinetic performance and cycle life while achieving high compaction density, thus laying a solid material foundation for the fabrication of ultra-high energy density battery cells.
[0018] Furthermore, in step S1, the solvent is at least one of deionized water, methanol, ethanol, or acetone.
[0019] Further, in step S1, the ball milling dispersion time is 20-40 min, and the target particle size D50 after nano-grinding is 360-400 nm; the roller kiln sintering temperature is 750-780℃, and the constant temperature time is 10-14 h. In step S2, the slurry is first dispersed using a ball mill for 20-40 min, and then ground to the target particle size (D50 is 360-400 nm) using a nano-grinding mill.
[0020] Furthermore, in step S2, the boron source is boric acid or borate, and the titanium source is titanate, titanium ammonium oxalate, or titanium dioxide sol.
[0021] Furthermore, in steps S1 and S2, the amount of boron source added is 0.5% to 1.5% of the total mass of the lithium iron phosphate matrix, and the amount of titanium source added is 1% to 4% of the total mass of the lithium iron phosphate matrix.
[0022] Further, in step S3, the spray mixing method is as follows: under the stirring of a high-speed mixer with a blade speed ≥1000 rpm, the boron-titanium mixed solution obtained in step S2 is sprayed in batches, with a total mixing time of 50~70 min. The "spraying in batches" method in step S3 is as follows: the boron-titanium mixed solution obtained in step S2 is sprayed into the high-speed mixer containing the lithium iron phosphate matrix in the form of a spray, with 2 ml of boron-titanium mixed solution sprayed every 5 min until all of it is sprayed, with a total mixing time of 50~70 min.
[0023] Furthermore, in step S4, the sintering temperature is 500~800℃, the heating rate is 5℃ / min, and the holding time is 6~12h.
[0024] Compared with the prior art, the technical solution of this application has at least the following beneficial effects:
[0025] This invention simultaneously introduces boron and titanium sources into the synthesis system of lithium iron phosphate (LFP). After mixing and sintering, a unique boron-titanium composite modification layer is designed and formed on the surface of LFP particles. Through the synergistic surface modification of boron and titanium, on the one hand, the low-temperature liquid phase formed by boron during sintering promotes the sphericity of LFP particles, significantly improving the compaction density and volumetric energy density of the powder; on the other hand, titanium is enriched on the particle surface to form a high-ionic-conductivity interface phase containing LiTi2(PO4)3, effectively suppressing excessive grain growth caused by the introduction of boron, while constructing a three-dimensional lithium-ion transport channel, greatly improving the interfacial kinetics and rate performance, and reducing side reactions between the electrode and the electrolyte. Ultimately, the material maintains high compaction density while possessing excellent cycle stability and high-rate discharge capability, making it suitable for the preparation of ultra-high energy density battery cells. Attached Figure Description
[0026] Figure 1 The distribution diagram of boron (B) and titanium (Ti) elements in the lithium iron phosphate cathode material prepared in Example 1 is shown.
[0027] Figure 2 The image shows the EDS spectrum of the lithium iron phosphate cathode material prepared in Example 1.
[0028] Figure 3 SEM image of the lithium iron phosphate cathode material prepared in Example 1;
[0029] Figure 4 SEM image of the lithium iron phosphate cathode material prepared in Comparative Example 1;
[0030] Figure 5 The 1C discharge capacity curves are for each embodiment. Detailed Implementation
[0031] The present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and technical features described in this application can be combined with each other. It should also be pointed out that, unless otherwise indicated, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. The terms "comprising" or "including" and similar words used in this invention refer to elements or objects preceding the word that encompass the elements or objects listed following the word and their equivalents, without excluding other elements or objects.
[0032] Example 1
[0033] The first aspect of this embodiment provides a lithium iron phosphate cathode material, including a lithium iron phosphate matrix and a boron-titanium composite modification layer coated on the surface of the lithium iron phosphate matrix.
[0034] The boron-titanium composite modification layer contains boron and titanium elements; the mass ratio of boron to titanium in the boron-titanium composite modification layer is 1:1.
[0035] The second aspect of this embodiment provides a method for preparing a lithium iron phosphate cathode material, including the following steps:
[0036] S1: Preparation of lithium iron phosphate matrix: Iron phosphate, lithium carbonate, sucrose, and polyvinylpyrrolidone (PVP) were sequentially added to deionized water and dispersed evenly, with Li:Fe = 1.030, residual carbon set at 1.3%, and the mass ratio of sucrose to PVP at 10:1, to obtain a slurry; then the slurry was dispersed in a ball mill for 20 min, and then ground in a nano-mill to a particle size D50 of 360 nm; after spray drying, it was sintered in a roller kiln at a sintering temperature of 750℃ for 10 h to obtain lithium iron phosphate matrix (LFP-C).
[0037] S2: Preparation of boron-titanium mixed solution: Weigh 0.28g boric acid and 0.36g titanate respectively, add them to 10ml deionized water and stir for 10min to form boron-titanium mixed solution, and put it into a spray bottle for later use;
[0038] S3: Mixing: Weigh 100g of the lithium iron phosphate matrix obtained in step S1 and add it to a small high-speed mixer. With the impeller speed of the high-speed mixer ≥1000rpm, after running the equipment, spray the boron-titanium mixed solution obtained in step S2 in the form of a spray. Spray 2ml of boron-titanium mixed solution every 5min until it is completely sprayed. The total mixing time is 50min to obtain the boron-titanium / lithium iron phosphate precursor.
[0039] S4: Sintering: The boron-titanium / lithium iron phosphate precursor obtained in step S3 is sintered in a nitrogen atmosphere at a temperature of 500℃, a heating rate of 5℃ / min, and a holding time of 6h to obtain a lithium iron phosphate cathode material (LFP-B / T / C) with a boron-titanium composite modification layer on the surface.
[0040] Example 2
[0041] The first aspect of this embodiment provides a lithium iron phosphate cathode material, including a lithium iron phosphate matrix and a boron-titanium composite modification layer coated on the surface of the lithium iron phosphate matrix.
[0042] The boron-titanium composite modification layer contains boron and titanium elements; the mass ratio of boron to titanium elements in the boron-titanium composite modification layer is 1:2.
[0043] The second aspect of this embodiment provides a method for preparing a lithium iron phosphate cathode material, including the following steps:
[0044] S1: Preparation of lithium iron phosphate matrix: Iron phosphate, lithium carbonate, sucrose, and polyvinylpyrrolidone (PVP) were sequentially added to deionized water and dispersed evenly, with Li:Fe = 1.030, residual carbon set at 1.3%, and the mass ratio of sucrose to PVP at 10:1, to obtain a slurry; then the slurry was dispersed in a ball mill for 30 min, and then ground in a nano-mill to a particle size D50 of 380 nm; after spray drying, it was sintered in a roller kiln at a sintering temperature of 765℃ for 12 h to obtain lithium iron phosphate matrix (LFP-C).
[0045] S2: Preparation of boron-titanium mixed solution: Weigh 0.28g of borate and 0.71g of titanium oxalate respectively, add them to 10ml of deionized water and stir for 10min to form a boron-titanium mixed solution, and put it into a spray bottle for later use;
[0046] S3: Mixing: Weigh 100g of the lithium iron phosphate matrix obtained in step S1 and add it to a small high-speed mixer. With the impeller speed of the high-speed mixer ≥1000rpm, after running the equipment, spray the boron-titanium mixed solution obtained in step S2 in the form of a spray. Spray 2ml of boron-titanium mixed solution every 5min until it is completely sprayed. The total mixing time is 60min to obtain the boron-titanium / lithium iron phosphate precursor.
[0047] S4: Sintering: The boron-titanium / lithium iron phosphate precursor obtained in step S3 is sintered in a nitrogen atmosphere at a temperature of 650℃, a heating rate of 5℃ / min, and a holding time of 9h to obtain a lithium iron phosphate cathode material (LFP-B / T / C) with a boron-titanium composite modification layer on the surface.
[0048] Example 3
[0049] The first aspect of this embodiment provides a lithium iron phosphate cathode material, including a lithium iron phosphate matrix and a boron-titanium composite modification layer coated on the surface of the lithium iron phosphate matrix.
[0050] The boron-titanium composite modification layer contains boron and titanium elements; the mass ratio of boron to titanium in the boron-titanium composite modification layer is 1:4.
[0051] The second aspect of this embodiment provides a method for preparing a lithium iron phosphate cathode material, including the following steps:
[0052] S1: Preparation of lithium iron phosphate matrix: Iron phosphate, lithium carbonate, sucrose, and polyvinylpyrrolidone (PVP) were sequentially added to deionized water and dispersed evenly, with Li:Fe = 1.030, residual carbon set at 1.3%, and the mass ratio of sucrose to PVP at 10:1, to obtain a slurry; then the slurry was dispersed in a ball mill for 30 min, and then ground in a nano-mill to a particle size D50 of 400 nm; after spray drying, it was sintered in a roller kiln at a sintering temperature of 780℃ for 14 h to obtain lithium iron phosphate matrix (LFP-C).
[0053] S2: Preparation of boron-titanium mixed solution: Weigh 0.28g boric acid and 1.42g titanium dioxide sol respectively, add them to 10ml deionized water and stir for 10min to form boron-titanium mixed solution, and put it into a spray bottle for later use;
[0054] S3: Mixing: Weigh 100g of the lithium iron phosphate matrix obtained in step S1 and add it to a small high-speed mixer. With the impeller speed of the high-speed mixer ≥1000rpm, after running the equipment, spray the boron-titanium mixed solution obtained in step S2 in the form of a spray. Spray 2ml of boron-titanium mixed solution every 5min until it is completely sprayed. The total mixing time is 70min to obtain the boron-titanium / lithium iron phosphate precursor.
[0055] S4: Sintering: The boron-titanium / lithium iron phosphate precursor obtained in step S3 is sintered in a nitrogen atmosphere at a temperature of 800℃, a heating rate of 5℃ / min, and a holding time of 12h to obtain a lithium iron phosphate cathode material (LFP-B / T / C) with a boron-titanium composite modification layer on the surface.
[0056] Comparative Example 1 (No composite modification layer is formed on the surface of the lithium iron phosphate cathode material)
[0057] This comparative example provides a method for preparing a lithium iron phosphate cathode material, including the following steps:
[0058] Preparation of lithium iron phosphate: Iron phosphate, lithium carbonate, sucrose, and polyvinylpyrrolidone (PVP) were sequentially added to deionized water and dispersed evenly, with Li:Fe = 1.030, residual carbon set at 1.3%, and the mass ratio of sucrose to PVP at 10:1 to obtain a slurry; then the slurry was dispersed in a ball mill for 20 min, and then ground in a nano-mill to a particle size D50 of 360 nm; after spray drying, it was sintered in a roller kiln at a sintering temperature of 750℃ for 10 h to obtain lithium iron phosphate (LFP-C).
[0059] Comparative Example 2 (without adding a titanium source, a boron composite modification layer is formed on the surface of the lithium iron phosphate cathode material)
[0060] This comparative example provides a method for preparing a lithium iron phosphate cathode material, including the following steps:
[0061] S1: Preparation of lithium iron phosphate matrix: Iron phosphate, lithium carbonate, sucrose, and polyvinylpyrrolidone (PVP) were sequentially added to deionized water and dispersed evenly, with Li:Fe = 1.030, residual carbon set at 1.3%, and the mass ratio of sucrose to PVP at 10:1, to obtain a slurry; then the slurry was dispersed in a ball mill for 20 min, and then ground in a nano-mill to a particle size D50 of 360 nm; after spray drying, it was sintered in a roller kiln at a sintering temperature of 750℃ for 10 h to obtain lithium iron phosphate matrix (LFP-C).
[0062] S2: Preparation of boron mixed solution: Weigh 0.28g of boric acid and add it to 10ml of deionized water. Stir for 10min to form a boron mixed solution and put it into a spray bottle for later use.
[0063] S3: Mixing: Weigh 100g of the lithium iron phosphate matrix obtained in step S1 and add it to a small high-speed mixer. With the high-speed mixer blade speed ≥1000rpm, after running the equipment, spray the boric acid solution obtained in step S2 in the form of a spray. Spray 2ml of boron mixed solution every 5min until all of it is sprayed. The total mixing time is 50min to obtain the boron / lithium iron phosphate precursor.
[0064] S4: Sintering: The boron / lithium iron phosphate precursor obtained in step S3 is sintered in a nitrogen atmosphere at a temperature of 500℃, a heating rate of 5℃ / min, and a holding time of 6h to obtain a lithium iron phosphate cathode material (LFP-B / C) with a boron composite modification layer on the surface.
[0065] like Figure 1 As shown, in the lithium iron phosphate cathode material prepared in Example 1, boron and titanium elements exhibit a uniform co-distribution on the particle surface, indicating that they successfully formed a composite modification layer rather than separate, batch-separated coating phases. Further combining... Figure 2 EDS energy dispersive spectroscopy analysis confirmed that the composite modified layer contained characteristic signals of both boron and titanium, proving the chemical composition of the boron-titanium composite modified layer. Figure 3 and Figure 4 The SEM morphology comparison shows that the lithium iron phosphate particles of Example 1 have higher sphericity and fewer sharp edges than those of Comparative Example 1, and the particle surface is smoother and rounder. This is attributed to the low-temperature liquid phase formed by boron during sintering, which promotes particle rearrangement and spheroidization, providing a structural basis for improving compaction density. Figure 5 The 1C discharge capacity curves of various embodiments are shown, among which Example 2 has the best capacity retention and discharge plateau, further verifying the improvement of rate performance by boron-titanium synergistic modification.
[0066] As shown in Table 1, the compaction density of Comparative Example 1 without the modified layer was 2.55 g / cc, and its 1C rate performance was 145.0 mAh / g. Examples 1 to 3 of this application, modified with a boron-titanium composite, all exhibited higher compaction densities, ranging from 2.66 to 2.73 g / cc, and superior 1C rate performance, ranging from 149.2 to 158.1 mAh / g. Compared to Comparative Example 2 with only boron modification, Examples 1 to 3 significantly improved the 1C discharge capacity while maintaining or increasing the compaction density. Example 2 reached 158.1 mAh / g, an increase of approximately 6.5% compared to Comparative Example 2's 148.4 mAh / g. This indicates that while single boron modification can increase the compaction density to 2.64 g / cc to a certain extent, it degrades the rate performance, with its 1C capacity only reaching 148.4 mAh / g. The introduction of titanium to form a boron-titanium composite modification layer effectively suppressed boron-induced excessive grain growth due to the grain boundary pinning effect and high ion conductivity gradient interface of titanium, and constructed a three-dimensional lithium-ion transport channel, thereby achieving a synergistic improvement in rate performance under high solid density. Among them, Example 2, with a boron to titanium mass ratio of 1:2, exhibited the best overall performance, with a high solid density of 2.71 g / cc, a 0.1C capacity of 163.7 mAh / g, and a 1C capacity of 158.1 mAh / g.
[0067] Table 1 Performance tests of different embodiments and comparative examples
[0068]
[0069] The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed application, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A lithium iron phosphate cathode material, characterized in that, It includes a lithium iron phosphate matrix and a boron-titanium composite modification layer coating the surface of the lithium iron phosphate matrix.
2. The lithium iron phosphate cathode material according to claim 1, characterized in that, The boron-titanium composite modification layer contains boron and titanium.
3. The lithium iron phosphate cathode material according to claim 1, characterized in that, In the boron-titanium composite modification layer, the mass ratio of boron to titanium is 1:(1~4).
4. A method for preparing the lithium iron phosphate cathode material as described in claim 1, characterized in that, Includes the following steps: S1: Preparation of lithium iron phosphate matrix: Iron source, lithium source and carbon source are added to solvent in sequence and dispersed evenly to obtain slurry; the slurry is ball-milled and dispersed, and then nano-milled to the target particle size; after spray drying, it is sintered in roller kiln to obtain lithium iron phosphate matrix; S2: Preparation of boron-titanium mixed solution: Add boron source and titanium source to deionized water and stir to form boron-titanium mixed solution; S3: Mixing: The lithium iron phosphate matrix obtained in step S1 is added to a high-speed mixer and spray-mixed with the boron-titanium mixed solution obtained in step S2 to obtain a boron-titanium / lithium iron phosphate precursor. S4: Sintering: The boron-titanium / lithium iron phosphate precursor obtained in step S3 is sintered in a nitrogen or argon atmosphere to obtain a lithium iron phosphate cathode material with a boron-titanium composite modification layer on the surface.
5. The method for preparing the lithium iron phosphate cathode material according to claim 4, characterized in that, In step S1, the solvent is at least one of deionized water, methanol, ethanol, or acetone.
6. The method for preparing the lithium iron phosphate cathode material according to claim 4, characterized in that, In step S1, the ball milling dispersion time is 20~40 min, and the target particle size D50 after nano-grinding is 360~400 nm; the roller kiln sintering temperature is 750~780℃, and the constant temperature time is 10~14 h.
7. The method for preparing the lithium iron phosphate cathode material according to claim 4, characterized in that, In step S2, the boron source is boric acid or borate, and the titanium source is titanate, titanium ammonium oxalate, or titanium dioxide sol.
8. The method for preparing the lithium iron phosphate cathode material according to claim 4, characterized in that, In steps S1 and S2, the amount of boron source added is 0.5% to 1.5% of the total mass of the lithium iron phosphate matrix; the amount of titanium source added is 1% to 4% of the total mass of the lithium iron phosphate matrix.
9. The method for preparing the lithium iron phosphate cathode material according to claim 4, characterized in that, In step S3, the spray mixing method is as follows: under the stirring of the high-speed mixer blade speed ≥1000rpm, the boron-titanium mixed solution obtained in step S2 is sprayed in the form of a spray, and the spraying is completed in batches, with a total mixing time of 50~70min.
10. The method for preparing the lithium iron phosphate cathode material according to claim 4, characterized in that, In step S4, the sintering temperature is 500~800℃, the heating rate is 5℃ / min, and the holding time is 6~12h.
Citation Information
Patent Citations
Preparation method of spherical boron-doped lithium iron phosphate positive electrode material
CN119430116A